Agroecosystem Sustainability: Developing Practical Strategies - Gliessman, Stephen (CRC Press, 2009)
Agroecologists from around the world share their experiences in the analysis and development of indicators of agricultural sustainability in Agroecosystem Sustainability: Developing Practical Strategies. The authors build on the resource-conserving aspects of traditional, local, and small-scale agriculture while at the same time drawing on modern ecological knowledge and methods. They define the relationship between agroecology and sustainable development.